Detailing Poverty Incidence through Fractals: Which of the Gross National Product or Multidimensional Poverty Index Explain Poverty Incidence Better? (Asia Pacific Journal of Social and Behavioral Sciences, 2013)
This paper attempts to explain poverty incidence of the 97 countries using fractal analysis. Gross National Product (GNP) and Multidimensional Poverty Index (MPI) of each country were used as poverty indicators. Fractal dimensions were obtained, compared and analyzed. The three variables have fractal characteristics of ruggedness and self-similarity. Results revealed that the ruggedness of poverty incidence across the countries is due to the ruggedness of the MPI, that is, the deprivation to basic services such as health, education, and standard of living affects the quality of living. Thus, MPIs explain poverty incidence more precisely. With this finding, implications to policymakers to alleviate poverty can be addressed.
Keywords: Fractal analysis, Gross National Product, Multidimensional Poverty Index (MPI), poverty indicators, spectrum